Evaluation of Lumbar Intervertebral Disk Disorders and Associated Risk Factors among Yemeni Patients Using Magnetic Resonance Imaging - Al-Khamesi, Mariam et al. (University of Science and Technology, Sana'a, Faculty of Medicine and Health Sciences, Radiology and Medical Imaging Technology Program, 2023)
This study aimed to evaluate lumbar intervertebral disk height and length in disk herniation and degeneration patient Among Yemeni population using Magnetic Resonance Image and to assess the association between herniation and degeneration of lumber disk and related risk factors [ age, BMI, gender, life style, occupation and smoking]. The design of this study was a prospective cross-sectional method, this study carried out in Sana'a city among radiology departments at different hospitals during the period of December,2023 to February 2024, the study sample included 300 patients who having lumber disorder and underwent lumber MRI scan, ,the study data including patients demographic and the measurements of herniation and degeneration of lumber disk.